IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AT SDN 32 UKKE'E (AS A DRIVING SCHOOL) IN SOPPENG DISTRICT - Bayangkara, Muh. Wira (Makkareso: Riset Pengabdian Masyarakat, 2023)
Ministry of Education and Culture. Education and Culture in Elementary Schools is literacy and numeracy. This school program is designed to support each school in creating generations of lifelong learners with Pancasila personality. The success of everything requires the role of a teacher. The method used in this research is a qualitative research method. Independent learning is not about learning as you like or as you please students, but independent learning is a system formed and created by the government. SDN 32 Ukku'e is a driving school in the Donri-donri sub-district, Soppeng. In this school there are two classes that do not use an independent curriculum, namely grade two and grade six, in the sense of an independent curriculum class at this school. In implementing the curriculum, students are given a learning process involving existing media, using school facilities and other teaching aids. Classes at this school have a reading corner in each class to encourage literacy in student.